Domains of father involvement, social competence and problem behavior in preschool children - Torres, N. (2014)
Many studies reported that father involvement is associated with a wide range of developmental outcomes, however evidence is weaker when controlling for correlated mother involvement and when using different informants to assess father involvement and children development. Our study aimed to research the association between father involvement and preschoolers’ social competence, controlling for mother involvement, family demographics, parental stress, time spent in day-care, existence of siblings and child’s characteristics. Participants were 295 children between 36-71 months of age, 52% girls, all living in resident-father families. Hierarchical multiple regression models were performed entering the predictors in three blocks: child related variables, family demographics and stress, father relative involvement with the child. Results suggest that father involvement in leisure activities outdoors is a direct predictor of social competence, and also of lower externalizing problems, especially for boys.